STUDY ON THE POSTCOLONIAL NOVELIST BAPSISIDHWA - Md.Wali Hasan (International Journal of Multidisciplinary Research and Studies, 2021)
In contemporary literary studies, the word "post-colonial" functions well as a critical category. The labels "Commonwealth Literature," "Anglophone Literature," "New Literature in English," "Third World Literature," and "Literature of the Developing Nations" have been gradually phased out in favour of it in recent years. Every single one of them is troublesome in one way or another. Even the concept of "post-colonial" is fraught with its own set of problems. The basic definition of the phrase, as well as its range of use, might be contested. Its application can be narrowed down for the purpose of this study to refer to an unequal relationship between rich nations and poor nations in a variety of domains, including social, psychological, political, economic, and cultural practises and patterns, as well as the articulation of the same in literature. No matter how the above sentence is construed, post-colonialism may be understood as an outgrowth of colonialism. Post-colonial literatures came into being as authors strove to create a new type of fiction inside the English language by combining new imagery and, most importantly, new rhythms. This led to the development of post-colonial literatures.